2008
DOI: 10.1111/j.1398-9995.2008.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin null mutations are associated with increased asthma exacerbations in children and young adults

Abstract: Background:  Filaggrin (FLG) null mutations are important genetic predisposing factors for atopic asthma and have recently been shown to influence controller and reliever medication needs in asthmatic children. Our objective was to study the role of FLG null alleles in asthma exacerbations.Methods:  FLG mutations R501X and 2282del4 were assayed in 1135 individuals ranging from 3 to 22 years old with asthma from Tayside and Dumfries, Scotland. Asthma exacerbations over the previous 6 months were also studied.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
2
32
0
2
Order By: Relevance
“…More recent studies have confirmed the association and identified additional mutations in the FLG gene that predispose to AD in European and Asian populations (64-67). FLG mutations have also been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy, and food allergy (68)(69)(70)(71)(72)(73), suggesting that FLG mutation-associated SC barrier defects lead to increased numbers of episodes of percutaneous allergen exposure (Figure 2). Interestingly, FLG mutations are not associated with asthma without eczema (70,71), and most of the identified asthma-associated genes are not associated with AD (74,75), suggesting that atopic asthma is a distinguishable sub-entity.…”
Section: Major Players In Sc Barrier Dysfunctionmentioning
confidence: 99%
“…More recent studies have confirmed the association and identified additional mutations in the FLG gene that predispose to AD in European and Asian populations (64-67). FLG mutations have also been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy, and food allergy (68)(69)(70)(71)(72)(73), suggesting that FLG mutation-associated SC barrier defects lead to increased numbers of episodes of percutaneous allergen exposure (Figure 2). Interestingly, FLG mutations are not associated with asthma without eczema (70,71), and most of the identified asthma-associated genes are not associated with AD (74,75), suggesting that atopic asthma is a distinguishable sub-entity.…”
Section: Major Players In Sc Barrier Dysfunctionmentioning
confidence: 99%
“…The individual contribution to the overall effect of the 2284del4 allele was lower than that observed for R501X , suggesting that patients carrying the R501X mutation have more severe asthma. Studying the same population (extended to include 1,135 individuals) showed that FLG mutations were associated with a twofold greater risk of exacerbations in children with asthma [ 50 ]. Similarly, exacerbations were signifi cant for the R501X , but not the 2282del4 mutation, and the combined genotype compared to the wild type, respectively.…”
Section: Flg Mutations and Asthma Severitymentioning
confidence: 96%
“…Notably, in a study of 411 Danish children with maternal asthmatic predisposition followed from birth until school age, carriers of R501X and 2282del4 had an almost two times increased risk of asthma exacerbations, which was expressed within the [ 49 ] 2007 Scotland 874 children with asthma FLG mutations increase the severity of asthma Basu et al [ 50 ] 2008 Scotland 1,135 children with asthma FLG mutations increase the risk of asthma exacerbations Marenholz et al [ 48 ] 2009 Germany 871 children FLG mutations predict future asthma in children with eczema and food sensitizations Bønnelykke et al [ 51 ] 2010 Denmark 411 children FLG mutations increase the risk of asthma exacerbations fi rst 1.5 years of life and, furthermore, had a marked and persistent increase in acute severe asthma exacerbations from 1 year of age [ 51 ]. Moreover, in a large study of children and young adults ( n = 874) with physician-diagnosed asthma attending primary and secondary clinics in 18 primary care practices and a secondary care asthma clinic in Scotland, R501X and 2282del4 carriers had a signifi cantly increased disease burden, both in terms of lung function, with a greater airway obstruction in the FLG null carriers, and in the intensity of medication required for disease control [ 49 ].…”
Section: Flg Mutations and Asthma Severitymentioning
confidence: 98%
“…Patients with FLG null alleles have been demonstrated to have an increased need for asthma medication and greater obstructive lung function impairment [ 38 ]. In addition, mild persistent asthma patients who are carriers of a FLG null allele have a nearly twofold higher risk of exacerbation with a need for oral steroid therapy compared to asthma patients with wild-type fi laggrin alleles [ 39 ]. This association is strongest when the patients have both asthma and AD, which further supports the role FLG mutations can play in permitting the atopic march.…”
Section: Filaggrin In Airway Disease: Allergic Rhinitis and Asthmamentioning
confidence: 99%